Rainfall, Agricultural Output and Persistent Democratization - Antonio Ciccone; Adilzhan Ismailov (Economica, 2021)
We examine the effect of rainfall on agricultural output and democratization in the world's most agricultural countries. As in the agricultural economics literature, we find that the relationship between rainfall and agricultural output has an inverted U-shape, as agriculture is harmed by both droughts and very wet conditions. We also find the effect of rainfall on agricultural output to be transitory. The relationship between rainfall and democratization is U-shaped in the short run, and this effect persists in the long run. Hence democratic transitions outlast the (transitory) rainfall shocks that started the democratization process. The U-shaped relationship between rainfall and democratization is consistent with rainfall affecting democratization through its (inverted-U-shaped) effect on agricultural output.
Keywords: 330